Critical reflection on the role of theater nurses in a multidisciplinary team for perioperative care in China - Xiao Xiao; Zhu She-Ning (Sciendo, 2019)
The aim of this article is to reflect on the role of theater nurses in a multidisciplinary team, understand the factors that have influenced theater nurses' practice, and improve the authors' clinical practice ultimately.